2020
DOI: 10.5812/aapm.96418
|View full text |Cite
|
Sign up to set email alerts
|

Can Pulsed Radiofrequency of the Occipital Nerves Cause Sedation? A New Perspective of Existing Knowledge

Abstract: Background Pulsed radiofrequency stimulation (PRF) of the greater and lesser occipital nerves (GON and LON) has neuromodulative and analgesic properties. Objectives The aim of this study was to investigate whether the PRF of the occipital nerves can cause sedation. Methods This is an observational case series study in Pain Management Unit of Attikon University Hospital. Patients suffering from primary headaches were scheduled for PRF of occip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…According to the literature, the operation is successful in about 90% -97% of cases. However, the success rate in RF ablation in previous studies was reported to be approximately 75% (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23); nonetheless, the success rate of 85% -95% was observed in the present case report. Nevertheless, surgical intervention is not usually performed as it is invasive, and general anesthesia is necessary and is associated with considerable pain in the postoperative period.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…According to the literature, the operation is successful in about 90% -97% of cases. However, the success rate in RF ablation in previous studies was reported to be approximately 75% (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23); nonetheless, the success rate of 85% -95% was observed in the present case report. Nevertheless, surgical intervention is not usually performed as it is invasive, and general anesthesia is necessary and is associated with considerable pain in the postoperative period.…”
Section: Discussioncontrasting
confidence: 65%
“…The RF therapy can be applied to relieve different chronic pain syndromes, such as post-amputation phantom limb pain, radicular pain in lumbar herniated disc prolapse, occipital neuralgia, and cluster headache (16)(17)(18)(19)(20), some of which described lumbar and thoracic sympatholysis (21). Herein, we report the case of a male patient with an age of 22 years undergoing thermal RF sympathectomy therapy for palmar hyperhidrosis of his right hand.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also shown that radiofrequency can induce changes in membranes and intracellular structures, thereby modifying the transmission of action potentials and perception of pain (1,3,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, leads are advanced to the thoracic (T8/T9) level, where they are programmed to achieve maximum paresthesia topographic coverage and leg pain alleviation. The power source, an implantable pulse generator (IPG) or radiofrequency unit, is then connected to the leads (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%